2015
DOI: 10.1016/j.jml.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Words, objects, and locations: Perceptual matching explains spatial interference and facilitation

Abstract: [NEEDS REVISING]Many common words have spatial associations (e.g., "bird," "jump") that, counterintuitively, hinder identification of visual targets at their associated location. For example, "bird" hinders identification at the top of a display. This spatial interference has been attributed to perceptual simulation: "bird" shifts attention upward and evokes the perceptual representation of a bird, which impairs target identification by preoccupying the visual system. We propose an alternative explanation base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 74 publications
3
45
1
Order By: Relevance
“…In conclusion, the Lancaster Sensorimotor Norms provide a valuable resource for researchers across a variety of fields. Use of these norms as semantic variables, whether as an aggregate measure of sensorimotor strength or as modality-and effector-specific ratings, will inform psycholinguistic models of word recognition and language processing (e.g., Connell & Lynott, 2016a;Estes, Verges, & Adelman, 2015;Speed & Majid, 2017; see also Connell & Lynott, 2016b, for a review). The parallels between the sensorimotor dimensions in the present norms and specific brain regions related to perceptual and action processing mean that close examination of the roles and interactions of each dimension will be able to inform theories of grounded representation and embodied semantics (e.g., Connell et al, 2018;Lievers & Winter, 2018;Rey, Riou, Vallet, & Versace, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the Lancaster Sensorimotor Norms provide a valuable resource for researchers across a variety of fields. Use of these norms as semantic variables, whether as an aggregate measure of sensorimotor strength or as modality-and effector-specific ratings, will inform psycholinguistic models of word recognition and language processing (e.g., Connell & Lynott, 2016a;Estes, Verges, & Adelman, 2015;Speed & Majid, 2017; see also Connell & Lynott, 2016b, for a review). The parallels between the sensorimotor dimensions in the present norms and specific brain regions related to perceptual and action processing mean that close examination of the roles and interactions of each dimension will be able to inform theories of grounded representation and embodied semantics (e.g., Connell et al, 2018;Lievers & Winter, 2018;Rey, Riou, Vallet, & Versace, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that processing up/down words can influence performance at visual tasks involving compatible vs. incompatible location (Estes, Verges, & Adelman, 2015;Estes, Verges, & Barsalou, 2008;Gozli, Chasteen, & Pratt, 2013;Ostarek & Vigliocco, 2017). Behavioral work has established that processing up/down words enhances spatial attention to the compatible location which often leads to facilitated detection and identification of visual targets in the primed location (Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012;Gozli et al, 2013;Ostarek & Vigliocco, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interference in the compatible location is typically observed when stimulus onset asynchrony between prime words and visual targets is short (< 400ms) and when they are semantically unrelated (Estes et al, 2015(Estes et al, , 2008Gozli et al, 2013). Recent eye-tracking studies found that up/down words speed up subsequent spatially compatible saccades (Dudschig et al, 2013;Dunn, 2016) and influence concurrent saccades in the congruent direction (Ostarek, Ishag, Joosen, & Huettig, in press), suggesting that processing these words pre-activates specific motor programs in saccade-related brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…RT measures that are blind to the online cognitive processes that unfold as congruence versus incongruence on multiple levels interacts and give only one piece of discrete information about their final outcome (Estes et al, 2008(Estes et al, , 2015Gozli et al, 2013;Ostarek & Vigliocco, 2017). Eye-tracking, by contrast, can reveal the dynamically emerging processes with the highest temporal resolution.…”
mentioning
confidence: 99%